Integrative Analysis of Multi-Omics Identified the Prognostic Biomarkers in Acute Myelogenous Leukemia - Zheng, Jiafeng; Zhang, Tongqiang; Guo, Wei; Zhou, Caili; Cui, Xiaojian; Gao, Long; Cai, Chunquan; Xu, Yongsheng (Frontiers in Oncology, 2020)
Background Acute myelogenous leukemia (AML) is a common pediatric malignancy in children younger than 15 years old. Although the overall survival (OS) has been improved in recent years, the mechanisms of AML remain largely unknown. Hence, the purpose of this study is to explore the differential methylated genes and to investigate the underlying mechanism in AML initiation and progression based on the bioinformatic analysis. Methods Methylation array data and gene expression data were obtained from TARGET Data Matrix. The consensus clustering analysis was performed using ConsensusClusterPlus R package. The global DNA methylation was analyzed using methylationArrayAnalysis R package, and differential methylated genes (DMGs) and differential expression genes (DEGs) were identified using Limma R package. Besides, the biological function was analyzed using clusterProfiler R package. The correlation between DMGs and DEGs was determined using psych R package. Moreover, the correlation between DMGs and AML was assessed using varElect online tool. And the overall survival and progression-free survival were analyzed using survival R package. Results All AML samples in this study were divided into three clusters at k=3. Based on consensus clustering, we identified 1146 CpGs, including 40 hypermethylated and 1106 hypomethylated CpGs in AML. Besides, a total 529 DEGs were identified, including 270 upregulated and 259 downregulated DEGs in AML. The function analysis showed that DEGs significantly enriched in AML related biological process. Moreover, the correlation between DMGs and DEGs indicated that 7 DMGs directly interacted to AML. CD34, HOXA7, and CD96 showed strongest correlation with AML. Further to explore three CpG sites cg03583857, cg26511321, cg04039397 of CD34, HOXA7, and CD96 which acted as the clinical prognostic biomarkers. Conclusion Our study identified three novel methylated genes in AML, also explored the mechanism of methylated genes in AML. Our finding may provide novel potential prognostic markers for AML.